Efficient authentication scheme with tag-identity protection for EPC Class 2 Generation 2 version 2 standards - Hung-Yu Chien (International Journal of Distributed Sensor Networks)
Various radio-frequency identification standards and products have been designed to meet various market needs. To satisfy various requirements and integrate important features of existent standards, EPCglobal (2013/11) announced the new Gen2 standard called EPC Class 2 Generation 2 version 2. Even though inheriting the name Gen2, Generation 2 version 2 goes far beyond the features and functions of Generation 2 version 1. Generation 2 version 2 is a super set of several existent radio-frequency identification standards. It opens up great opportunities of novel radio-frequency identification applications that could not be implemented using conventional radio-frequency identification standards and products. In this article, we introduce the new standards and propose one new mutual authentication scheme which protects tags’ identifications. This scheme is the first radio-frequency identification authentication that could protect tags from unauthorized tracing and unauthorized identification using coming standard-based products. The analysis shows that the proposed scheme owns better performance than their counterparts in the multi-tag setting.